2012
DOI: 10.1016/j.tet.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on stereospecific fluorination at the 2′-arabino-position of a pyrimidine nucleoside: radiosynthesis of 2′-deoxy-2′-[18F]fluoro-5-methyl-1-β-d-arabinofuranosyluracil

Abstract: Direct fluorination at the 2′-arabino-position of a pyrimidine nucleoside has been a long-standing challenge, yet we recently reported such a stereospecific fluorination for the first time in the synthesis of [18F]FMAU, albeit in low yields. Herein we report the results of an investigation on stereospecific fluorination on a variety of precursors for synthesis of [18F]FMAU. Several precursors were synthesized in multiple steps and fluorination was performed at the 2′-arabino position using K[18F]/kryptofix 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…The choice of the leaving group as well as the protecting group is based on a previous study [10] that found that 3'/5'-THP-protection of uridine derivatives gave the best radiochemical yields and a 2'-mesyl group an appropriate balance between stability and leaving group abilities. Furthermore, our pilot studies showed that the appropriate tosyl-and nosyl-containing counterparts already decomposed during purification.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The choice of the leaving group as well as the protecting group is based on a previous study [10] that found that 3'/5'-THP-protection of uridine derivatives gave the best radiochemical yields and a 2'-mesyl group an appropriate balance between stability and leaving group abilities. Furthermore, our pilot studies showed that the appropriate tosyl-and nosyl-containing counterparts already decomposed during purification.…”
Section: Synthesismentioning
confidence: 99%
“…[9] However, this synthetic approach limits reliable and reproducible production on commercially available synthesis modules for human application. [10] For instance, multiple steps after 18 F introduction with an additional purification step due to the formation of the D-and Lisomers, as well as the use of toxic substances such as hydrogen bromide, make the translation to automated synthesizers difficult. These challenges go hand in hand with reproducibility issues when it comes to Quality Control (QC) in clinical practice according to the British/European/American Pharmacopeia (BPh/Ph.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bromination and subsequent condensation of 12 with the appropriate 2,4‐ bis‐O –(trimethylsilyl)pyrimidine followed by deprotection produced a mixture of the desired β ‐anomers and α ‐anomers 3 and 3b in a ratio of 3/1 to 8/1 depending on the reaction solvent, obtaining a radiochemical yield up to 45% of the correct stereoisomer . Even though the nucleoside radiotracers were obtained in good radiochemical yields and high purities, this synthetic approach reveals issues that inhibit these PET probes from being produced on commercially available synthesis modules for routine production and human application . For instance, multiple steps after [ 18 F]‐introduction with an additional purification step due to the formation of the d ‐isomers and l ‐isomers, as well as the use of toxic substances such as HBr, make the translation to automated synthesisers difficult.…”
Section: Introductionmentioning
confidence: 99%